Edukasi Infeksi Saluran Pernapasan Atas Di Posyandu Margosari - Naurah Romadlanti; Dwi Novitasari; Nurfitria Sholiha; Vagnessa Vaginleira; Putri Dwi Minantry; Fadlul Ichsan; Danendra Nezar Aristiananda; Anjas Sanjaya; Anton Suhendro (Kolaborasi: Jurnal Pengabdian Masyarakat, 2023)
Introduction: Upper Respiratory Tract Infection (ARI) is an acute respiratory infection caused by pathogens that are transmitted from human to human. Signs and symptoms usually appear quickly within a few hours to a few days. ARI is a very contagious disease and can occur due to decreased body resistance, for example due to fatigue or stress. Upper Respiratory Tract Infection (ARI) is one of the diseases that has the highest incidence rate and is the main cause of death and morbidity in infants and toddlers in Indonesia. Providing education to mothers of babies and toddlers regarding Upper Respiratory Tract Infections (ARI) is important. Objective: To provide counseling and education at toddler posyandu. Method: The strategy used is to carry out health education, where this strategy will be aimed directly at the target, namely mothers of babies and toddlers at Posyandu Balita Margosari RW. 05 Ledug Village. The implementation strategy that has been carried out is by providing health counseling on URTI, with lecture, discussion, and roleplay methods. Result: implementation of health education on Upper Respiratory Tract Infections at the Margosari Toddler Posyandu. Before being given counseling, many participants still did not know or hear about ISPA. After health education, participants already know about the meaning of ISPA infection, pathophysiology of ISPA, risk factors for ISPA, symptoms of ISPA, management of ISPA at home, prevention of ISPA, chest physiotherapy and massage for babies. Conclusion: The counseling material provided is about URTI which includes understanding, pathophysiology, signs and symptoms, risk factors for occurrence, management, and prevention, as well as chest physiotherapy in infants and toddlers. Counseling is carried out using leaflet media, ppt, and baby phantoms